Reliability analysis of corroded beams with FRP laminates. (2021) - Leema Rose, A.; Elango, D.; Vijayan, D.S.; Jebasingh Daniel, J.
Abstract: The term reliability and structural performance means the probability of the structure performing its intended function during its expected life time under the environmental conditions to which it is exposed. Reliability- based techniques can be used to account for the randomness in important variables that affect the strength of FRP strengthened RC beams. The use of such methods in structural engineering has greatly increased as reliability based models have been better properly understood and more widely accepted. Various parameters in GFRP strengthened corrosion-damaged RC beams are validated through reliability index by using simulation techniques and goodness of fit tests. Simulation is the technique of virtual testing of the validity of a physical phenomenon/structural design/mathematical equation without actually performing the experiment to obtain the values of the variables involved but by generating them through a mathematically tractable process called random number generation.